PENGARUH EKSTRAK ETANOL DAUN RAMANIA TERHADAP INSULIN DAN GDP PADA TIKUS OBESITAS DM TIPE 2 - Ramadhani, Aulia; Hidayat, Rahmat; Khaira, Dicky Septiannoor (Poltekkes Kemenkes Bandung, 2025)
Obesity is a major nutritional issue that can trigger insulin resistance, hyperlipidemia, and contribute to Type 2 Diabetes Mellitus (T2DM). Ramania leaves, rich in antioxidants such as flavonoids, have potential as antidiabetic and anti-obesity agents. This study aimed to evaluate the effects of ethanol extract of Ramania leaves on insulin levels and fasting blood glucose (FBG) in obese rats with T2DM. The research employed a true experimental laboratory method with a Randomized Pre-Posttest Control Group design to examine the effects of Ramania leaf ethanol extract on insulin levels and FBG in male Wistar rats (Rattus norvegicus) with obesity-induced T2DM. The study was conducted over six weeks at the PSPG Laboratory of Gadjah Mada University. Subjects were divided into six groups: KNo (normal control, non-obese model group), KN (negative control, obese T2DM rats), KP (positive control, obese T2DM rats treated with metformin), and P1, P2, and P3 (obese T2DM rats treated with Ramania leaf extract at doses of 150,300, and 600 mg/kg BW for 14 days). Obesity and T2DM induction were conducted using a high-fat diet for 14 days, followed by streptozotocin administration at 45 mg/kg BW/day for three days. ANOVA testing revealed significant differences between groups (P<0.000), demonstrating the effectiveness of Ramania leaf ethanol extract (EEDR). Treatment with EEDR significantly increased insulin levels across all treatment groups (KP,P1,P2,P3) compared to the negative control (KN), highlighting the potential of EEDR in insulin regulation for obese T2DM rats. Ramania leaf extract showed significant potential in enhancing insulin levels and reducing FBG levels.